ACTIVITIES EVALUATION OF SILVER NANOPARTICLE SYNTHESIZED USING ETHANOL EXTRACT OF PAPAYA LEAVES AS COSMETICS INGREDIENT - Mustofa Ahda; Narwanti, Iin; Mantoro, Rizki Dwi (International Journal of Allied Health Sciences, 2019)
Silver nanoparticles (AgNPs) synthesised using ethanol extracts of Carica papaya L. leaf to develop and exploit the ethanol extract of 70% and 96% of Carica papaya L. as bioreduction in the synthesis of AgNPs resulting the antioxidant and antibacterial activity. The antioxidant activity was determined using the DPPH method measured by UV-Vis spectrophotometer and the IC50value was determined. While the antibacterial activity of AgNPs was determined by the inhibitory zone diameter of Staphylococcus aureus. The result of this research showed that AgNps biosynthesised from 70% and 96% ethanol extract of Carica papaya L. leaf able to inhibit the free radicals of DPPH with IC50 values of 1415.12 Âµg/mL and 1351.22 Âµg/mL respectively. While, both 70% and 96% ethanol extract also inhibit the Staphylococcus aureus bacterial growth within 5.40 mm and 6.27 mm, respectively. To sum up, although the AgNPs produced have low antioxidant activity, both extracts have the bacterial activity of Staphylococcus aureus.